Liquid Biopsy in Non-Small Cell Lung Cancer - Molina-Vila, Miguel A.; Mayo-de-las-Casas, Clara; Giménez-Capitán, Ana; Jordana-Ariza, Núria; Garzón, Mónica; Balada, Ariadna; Villatoro, Sergi; Teixidó, Cristina; García-Peláez, Beatriz; Aguado, Cristina; Catalán, María José; Campos, Raquel; et al. (Frontiers in Medicine, 2016)
Liquid biopsy analyses are already incorporated in the routine clinical practice in many hospitals and oncology departments worldwide, improving the selection of treatments and monitoring of lung cancer patients. Although they have not yet reached its full potential, liquid biopsy-based tests will soon be as widespread as "standard" biopsies and imaging techniques, offering invaluable diagnostic, prognostic and predictive information. This review summarizes the techniques available for the isolation and analysis of circulating-free DNA and RNA, exosomes, tumor-educated platelets and CTCs from the blood of cancer patient, presents the methodological challenges associated with each of these materials and discusses the clinical applications of liquid biopsy testing in lung cancer.